The Discovery of LML134, a Histamine H3 Receptor Inverse Agonist for the Clinical Treatment of Excessive Sleep Disorders. (21st May 2019) - Troxler, Thomas; Feuerbach, Dominik; Zhang, Xuechun; Yang, Charles R.; Lagu, Bharat; Perrone, Mark; Wang, Tie‐Lin; Briner, Karin; Bock, Mark G.; Auberson, Yves P.
Abstract: Histamine H3 receptor (H3R) inverse agonists that have been in clinical trials for the treatment of excessive sleep disorders, have been plagued with insomnia as a mechanism‐based side effect. We focused on the identification of compounds that achieve high receptor occupancy within a short time, followed by rapid disengagement from the receptor, a target profile that could provide therapeutic benefits without the undesired side effect of insomnia. This article describes the optimization work that led to the discovery of 1‐(1‐methyl‐6‐oxo‐1, 6‐dihydropyridazin‐3‐yl)piperidin‐4‐yl 4‐cyclobutylpiperazine‐1‐carboxylate (18 b, LML134). Abstract : Wake up, enjoy the day and sleep again ! The histamine H3 receptor inverse agonist LML134 (18 b ) achieves rapid oral absorption and brain penetration, leading to strong wakefulness‐enhancing effects in rats. It also rapidly disengages from the receptor, a desirable profile to limit the risk of insomnia during the night following treatment. Clinical trials are ongoing to confirm its clinical efficacy in humans.